Dari Laut ke Darat : Dialektika Eksklusi dan Inklusi Sosial Suku Sawang di Belitung Timur - Fuji Riang Prastowo; Elok Anggraini; Masdar Faridl; Ahmad M Arrozy (Universitas Andalas, 2022)
This study aims to investigate about how the dialectic of social exclusion and inclusion occurs in the Sawang Tribe in East Belitung after relocating their living space from sea to land. The Sawang Tribe is a Sea Tribe in the waters of Bangka Belitung since the era of the Sriwijaya Kingdom, then settled on the mainland after being contracted as PT Timah workers in the Dutch colonial era. This study uses the Phenomenology-Based Ethnography method with data collection for two months in 2019 using live-in participatory observation with the Sawang Tribe in Seberang, Selinsing Village, Gantung District, East Belitung Regency, Indonesia. The results of the study conclude that the process of land settlement is very significant causing a number of risks to the living space of the Sawang Tribe. Social exclusion is caused by the stigma resulting from interactions between ethnic groups who view the unnatural behavior of sea people living on land. Meanwhile, the process of social inclusion is dominated by the psychosocial domain, which views the ethos of the Sawang Tribe as helpers and hardworkers, as well as experts in supernatural abilities.